1999
DOI: 10.1108/17465729199900006
|View full text |Cite
|
Sign up to set email alerts
|

‘Just Because I Like it Doesn't Mean it has to Work’: Personal Experiences of an Antenatal Psychosocial Intervention Designed to Prevent Postnatal Depression

Abstract: The antenatal psychosocial intervention to prevent postnatal depression, Preparing for Parenthood, was evaluated in an additional qualitative study of the participants' experience of the classes. This was to complement the findings of the core study with respect to the intervention's immediate impact on their emotional well‐being. All the women interviewed who attended the intervention considered it a positive experience. However, initial indications are that the intervention did not decrease, overall, the lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(35 citation statements)
references
References 7 publications
1
34
0
Order By: Relevance
“…Session feedback indicated that the essential intervention components had been covered by the course leaders (Brugha, et al 1998 b ;Wheatley & Brugha, 1999). However, it is possible that the brief training organized for the course leaders and their lack of experience in structured psychological interventions may have caused shortcomings in delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Session feedback indicated that the essential intervention components had been covered by the course leaders (Brugha, et al 1998 b ;Wheatley & Brugha, 1999). However, it is possible that the brief training organized for the course leaders and their lack of experience in structured psychological interventions may have caused shortcomings in delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Partners' input away from the intervention setting was reported as valuable in interventions where learning strategies were the key component (Migl, 2009), and, additionally, this activity was credited as serving to improve communication between the women and their partners. Recipients also reported that the intervention helped them to harness support from family members (Gao et al, 2012;Wheatley and Brugha, 1999).…”
Section: Supportmentioning
confidence: 99%
“…Specifically, this support came in the form of emotional and informational support derived from sharing experiences, the normalisation of experiences by other group members (Wheatley et al, 2003;Wheatley and Brugha, 1999) and exchanging advice (Andersson et al, 2012;Kennedy et al, 2009;Klima et al, 2009;Lehman, 2012;McNeil et al, 2012McNeil et al, , 2013Novick et al, 2012;TannerSmith et al, 2012;Teate et al, 2011). Service providers (Shanok, 2007;Wheatley and Brugha, 1999), also reported that the intervention was effective when the group was supportive. Few women reported a dislike for a peer group environment, and in these cases this appeared to be due to a preference for privacy (Andersson et al, 2012;Wheatley et al, 2003).…”
Section: Supportmentioning
confidence: 99%
See 2 more Smart Citations